AR-V7-Driven Mitochondrial Metabolic Reprogramming in Enzalutamide-Resistant Prostate Cancer: Mechanisms and Therapeutic Implications - Rongxin Chang; Zhuangzhuang Zhang (Serican Journal of Medicine, 2026)
Enzalutamide resistance in castration-resistant prostate cancer (CRPC) is frequently driven by androgen receptor splice variant 7 (AR-V7), a prognostic biomarker that lacks the ligand-binding domain and evades enzalutamide inhibition; however, the downstream metabolic networks sustaining resistant-cell survival remain incompletely understood. This review summarizes AR-V7 structural features, non-canonical transcriptional programs, and resulting mitochondrial dysfunction. AR-V7 occupies distinct chromatin-binding sites, preferentially activating genes involved in oxidative phosphorylation (OXPHOS), glutamine metabolism, and redox homeostasis while repressing tumor-suppressive metabolic genes. This dual transcriptional mode yields a bidirectional mitochondrial phenotype: hyperactive OXPHOS and enhanced antioxidant defense coexist with mitochondrial structural damage and ferroptosis evasion. Consequently, AR-V7-positive tumors exhibit high mitochondrial dependency, representing a targetable vulnerability. Preclinical strategies—including electron transport chain complex I inhibition, glutaminase blockade, copper ionophore-induced cuproptosis, and AR-V7-targeted degradation—show promise in enzalutamide-resistant models, but normal tissue toxicity, metabolic plasticity, dynamic AR-V7 expression, and lack of validated biomarkers remain translational obstacles. In conclusion, AR-V7-driven mitochondrial metabolic remodeling is central to enzalutamide resistance; future studies should dissect AR-V7–mitochondria regulatory nodes and optimize mitochondria-targeted combination strategies.